Red de datos de fibra óptica redundante para la comunicación de los servicios del sistema de gestión industrial de la Fabrica Impaecsa-Essity, Sede Babahoyo. - Benites Cruz, Carlos Rafael (2023)
The present research focused on the fact that effective communication in an industrial environment is crucial for the continuous and efficient functioning of production processes. This thesis focuses on the implementation of a redundant fiber optic infrastructure in the IMPAECSA-ESSITY factory in Babahoyo. Redundancy in fiber optic infrastructure is considered essential to improve the reliability and availability of service communication in the industrial management system. An implementation of this type of redundant infrastructure has demonstrated a notable improvement in the availability of communication services. Downtime has been significantly reduced, which in turn has improved production continuity in the factory. The choice of high-quality components and the ring topology have increased resistance to failure, ensuring reliable communication. Performance evaluation and testing have supported the effectiveness of redundant fiber optic infrastructure. This approach has proven to be an efficient strategy to maintain efficiency and quality in the industrial process. The thesis highlights the importance of investing in redundant communications infrastructure in critical industrial environments.